Maresin 1 Mitigates Sepsis-Associated Acute Kidney Injury in Mice via Inhibition of the NF-κB/STAT3/MAPK Pathways - Sun, ShuJun; Wang, JiaMei; Wang, JingXu; Wang, FuQuan; Yao, ShangLong; Xia, HaiFa (Frontiers in Pharmacology, 2019)
Acute kidney injury (AKI) is one of the most common and serious complications of sepsis, in which the inflammatory cascade plays a crucial role. There is now increasing evidence that lipid mediators derived from the omega-3 fatty acid docosahexaenoic acid (DHA) have potent anti-inflammatory effects that promote the timely regression of acute inflammation. In this study, we investigated the protective effects and molecular mechanism of a novel pro-inflammatory regression mediator Maresin 1 (MaR1) on acute kidney injury in septic mice. The cecal ligation and puncture (CLP) was used to establish a mice model of sepsis. As a result, we found that MaR1 significantly increased the seven-day survival rate of septic mice and the anti-inflammatory factor IL-10, while reduced bacterial load and pro-inflammatory cytokines (TNF-α, IL-6 and IL-1β). In addition, MaR1 dose-dependently reduced renal injury scores and serum creatinine and urea nitrogen levels in septic mice, meanwhile inhibiting renal neutrophil infiltration and MPO activity. In terms of signaling pathway, we found that MaR1 inhibits the expression of phosphorylated p65, Stat3, JNK, ERK, and p38, and significantly reduces nuclear p65 activity. In conclusion, our results indicate that MaR1 is able to reduce neutrophil infiltration and inhibit NF-ΚB/STAT3/MAPKs activity and reduce inflammatory factor levels to accelerate the regression of inflammation and thereby weaken sepsis-associated acute kidney injury in mice.